(untitled) (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2021)
The problems of quality assurance of Islamic education at the higher education level are related to the meaning of quality assurance, regulation, implementation, independent standards, and quality culture. This study aims to determine the planning, organizing, implementing, and controlling of education quality assurance at Fakultas Agama Islam Universitas Islam Sumatera Utara. The type of research is qualitative research. Data was collected by observation, interviews, and document studies. Data analysis is done by compiling, connecting, reducing, presenting and concluding. The findings show that Fakultas Agama Islam Universitas Islam Sumatera Utara implements quality assurance which philosophically refers to the Deming quality cycle, namely: plan, do, check, action. Practically based on regulations, quality assurance is carried out through four stages, namely: planning, organizing, implementing, and controlling quality assurance. Quality assurance planning is carried out by involving university leaders, faculty leaders, lecturers, faculty senate, experts, students and stakeholders in the preparation of vision, mission, policies, standards, and quality documents. Organization of quality assurance is carried out by allocating resources, implementing education and training, and monitoring organizational effectiveness. Implementation of quality assurance is carried out by strengthening quality leadership and managerial functions